Nigeria, Zimbabwe and the Struggle for Black Majority Rule in South Africa - Osarumwense, Charles O. (Àgídìgbo: ABUAD Journal of the Humanities, 2018)
This work examines the contribution of Nigeria and Zimbabwe to the liquidation of apartheid and institutionalised racism in South Africa. It analyses the diplomatic engagement of both countries in intergovernmental organizations such as the UN, OAU and the Commonwealth in the struggle for the establishment of racial equality and democracy in South Africa. The work highlights the cooperation of Nigeria and Zimbabwe in efforts to end apartheid and racism in South Africa. Both countries were committed to pan-Africanism and united in commitment to anti-colonialism and racial equality and this made them to cooperate in the anti-apartheid struggle. A number of works exist on Nigeria’s role in the anti-apartheid struggle in South Africa, but there is hardly any that focuses on the cooperation between Nigeria and Zimbabwe in the struggle to end racism in the country. Anti-colonialism and racial equality were important foreign policy objectives that Nigeria adopted from independence in 1960 and this made her to be involved in the independence struggle in Zimbabwe. Nigeria’s involvement in the independence movement in Zimbabwe contributed tremendously to Zimbabwe’s independence in 1980 and following Zimbabwe’s independence, both countries worked together to assist other African territories still under colonial rule. The work utilizes mainly oral sources, government records, reports of international organizations, newspaper reports and journal articles as sources of information. The work maintains that cooperation between Nigeria and Zimbabwe contributed extensively to the establishment of racial equality and democracy in South Africa in 1994. The study concludes that African states can build on the ideals of pan-Africanism to address contemporary problems as they did in the struggle against apartheid from the 1960s to the 1990s.